奈米接面系統的簡併電子與磁自旋電子的輸運性質 - 陳煜璋; Chen Yu-Chang (My University, 2010)
本研究計畫為三年期的計畫。計畫內容區分為兩部分：第一部分是分子電子學的 研究。以我們過去所發展關於分子電子學第一原理計算與多體理論作為研究基礎，繼續 探討奈米接面系統的電子傳輸性質，如閘極效應、local heating, shot noise, inelastic current, current induced force 等多體效應，並進一步研究分子電晶體的可行性與機制。第二部分 是分子自旋電子學的研究。我們計畫將我們目前分子自旋簡併系統的理論和計算，推廣 到分子磁自旋系統的理論和計算。我們計畫將分子系統的金屬電極以磁性金屬電極取 代，並且考慮原子的自旋軌道偶合效應。由於此系統的尺度微小，所以電子自旋容易保 存，加上電子隧穿特性的影響，此系統的TMR (tunneling magnetoresistance)效應預期會 很顯著，這也是我們投入分子系統的自旋電子輸運理論研究的原因。我們預期此系統是 有潛力應用於奈米級磁自旋電子元件的製作，例如spin field effect transistor(SFET)等自 旋電子元件等。我們計畫以密度泛函理論(DFT)計算方式，計算分子電子自旋系統的接 面性質，研究電子磁自旋的輸運性質並探討此新穎系統的多體物理現象。我們將探討磁 自旋分子元件的物理機制與材料特性，朝著分子磁自旋電子元件設計的方向努力。奈米 接面系統的電子磁自旋輸運性質，這是一個非常新穎的研究領域，需要開發新的理論與 程式，是非常有趣且具挑戰性的研究工作。

In this 3-year project, we propose to study the transport properties in nano scale junctions. This project can be casted into two categories: spin-unpolarized transport and spin-polarized transport. For spin degenerate case we plan to continue our previous works on the transport properties in nano scale junctions. We will investigate the properties of electron transport in atomic/molecular bimetal junction, including the effect of gate field and many-body effects occurred in this system. We will study the fundamental physical phenomena happened in nano junction, such as effects of local heating, inelastic current, shot noise, and current induced force. All these basic research can contribute to understand the fundamental physics in nanojunction and directed towards the design of new form of electronics devices based on atom/molecule system. In addition, we will extend our research to the transport properties of spin-polarized electrons in nano scale junction. We propose to develop new theories and new codes in the framework of density functional theory to study possible molecular spintronics devices.” Molecular spintronics” is a brand new field and we expect that it is the way for us to stay in the frontier researches. We plan to investigate the role of spin electrons played in the molecular junction. For example, we plan to replace the metal eletrodes by ferromagnets and study tunneling magnetoresistans (TMR). Due to the nature of tunneling and small size of this system, spin is easy to preserve and large magnetoresitance can be anticipated. As a result, molecular system may be a good candidate for spin field effect transistor (SFET). In the long run, we will devote to probe the possibility of new form of spin electronic devices at atomic/molecule scale based on our researches.
Spin Polarized Transport and Spin Unpolarized Transport in Nano Junctions